Marketing at the confluence between entertainment and analytics : proceedings of the 2016 Academy of Marketing Science (AMS) World Marketing Congress - Rossi, Patricia (Springer, 2017)
This volume presents the full proceedings of the 2016 Academy of Marketing Science (AMS) World Marketing Congress held in Paris, France. It contains current research in marketing from academics, scholars, and practitioners from around the world. Focusing on advancing marketing theory and practice, this volume will help marketers to move forward in providing value for companies, consumers, and society. Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses, and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complementing the Academy's flagship journals, the Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science.
Keywords: Marketing -- Congresses.; Marketing -- Management -- Congresses.; elektronické knihy; electronic books